Strategies for biodiversity maintenance value at recreation area by SWOT model - Karimzadegan, Hasan (Pure and Applied Science Advances, 2018)
This research, strategies for biodiversity maintenance at recreation area by SWOT model in Iran, is a field study for determining strength/weak points and also any opportunities and threats by SWOT method through presenting required strategies for recognition of tourism promotion strategies and maintenance of biodiversity at Recreation area. According to data analysis, it is concluded that 67.5% of tourists prefer spring and 27.4% of them prefer summer, 4.7% prefer autumn and 0.3% prefer winter for their trips. This is based upon weak facilities of the area which makes it difficult for tourists to have any trips at cold season. In case of a correct programming, it is possible to modify managerial organizations and powerful advertisement by mutual cooperation of concerned organizations and authorities with tourism and people. The above-mentioned factors are the most important strategies of promotion for maintenance of biodiversity in this area.